2017
DOI: 10.1111/jace.14888
|View full text |Cite
|
Sign up to set email alerts
|

Intense upconversion luminescence and energy‐transfer mechanism of Ho3+/Yb3+ co‐doped SrLu2O4 phosphor

Abstract: A series of novel SrLu 2 O 4 : x Ho 3+ , y Yb 3+ phosphors (x=0.005-0.05, y=0.1-0.6) were synthesized by a simple solid-state reaction method. The phase purity, morphology, and upconversion luminescence were measured by X-ray diffraction (XRD), scanning electron microscopy (SEM), and photoluminescence (PL) spectroscopy. The doping concentrations and sintering temperature were optimized to be x=0.01, y=0.5 and T=1400°C to obtain the strongest emission intensity. Under 980 nm laser diode excitation, the SrLu 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…1 xRe 3+ . [9][10][11][12][13][14][15][16][17] The following explanations may contribute to the existence of rare oxides as impurities: Lu 2 O 3 has low reactivity and is in excess in the raw materials according to the stoichiometric ratio of Sr 1−x Ln 2 O 4 :xRe 3+ . After sintering, the excess Lu 2 O 3 in the raw materials is left as an impurity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 xRe 3+ . [9][10][11][12][13][14][15][16][17] The following explanations may contribute to the existence of rare oxides as impurities: Lu 2 O 3 has low reactivity and is in excess in the raw materials according to the stoichiometric ratio of Sr 1−x Ln 2 O 4 :xRe 3+ . After sintering, the excess Lu 2 O 3 in the raw materials is left as an impurity.…”
Section: Resultsmentioning
confidence: 99%
“…11 Under 980 nm laser diode excitation, the SrLu 2 O 4 :Ho 3+ ,Yb 3+ phosphors exhibit an intense green upconversion emission band centered at 541 nm and weak red emission that peaked at 673 nm, and Songbin Liu et al hold the view that Ho 3+ , Yb 3+ ions occupied Lu 3+ sites. 17 The activator ions were all considered occupying only one site in the respective reports. In our previous work, we reported a blue phosphor, SrLu 2 O 4 :Ce 3+ , with great thermal stability and fabricated a white LED with a high color rendering index (CRI), 18 and we also found that there were two luminescence centers in this phosphor and this phenomenon was not mentioned in the previous reports about SrLn 2 O 4 type phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…Next, Ho 3+ ions in the upper levels can emit bright green (~553 nm) and relatively weak red (~669 nm) UCL through 5 F4, 5 S2 → 5 I8 and 5 F5 → 5 I8 processes, respectively [48], [49]. Moreover, there is a strong energy back transfer (EBT): 5 F4, 5 S2 (Ho 3+ ) + 2 F7/2 (Yb 3+ ) → 5 I6 (Ho 3+ ) + 2 F5/2 (Yb 3+ ) between Yb 3+ ions and Ho 3+ ions, which decreased the population of Ho 3+ ions at 5 F4, 5 S2 and affected the lifetime of UCL [22], [28].…”
Section: Ucl Mechanisms Of Y2o3:yb 3+ /Ho 3+ Ucnpsmentioning
confidence: 99%
“…8(a) and (b) that the lifetime of green UCL exhibits a gradual decline trend as increasing the Yb 3+ concentration, which drops from 374.06 to 143.21 μs. It is powerful evidence to show the existence of EBT process 5 F4, 5 S2 (Ho 3+ ) + 2 F7/2 (Yb 3+ ) → 5 I6 (Ho 3+ ) + 2 F5/2 (Yb 3+ ) between Yb 3+ ions and Ho 3+ ions [22], [28]. The EBT process will cause depopulation of the 5 F4, 5 S2 state so that the green UCL lifetime decrease.…”
Section: Ucl Mechanisms Of Y2o3:yb 3+ /Ho 3+ Ucnpsmentioning
confidence: 99%
“…3,4 Owing to their abundant ladder-like energy levels and relatively long excited-state lifetimes, trivalent RE ions such as Er 3+ , Tm 3+ or Ho 3+ are usually selected as activators. 5 However, one of the drawbacks of the above RE 3+ ions is that they have low absorption cross-sections for 4f-4f transitions, which result in the low luminescence intensity for these transitions. 6 Yb 3+ ions are commonly used as sensitizers in UC luminescence materials due to their relatively large absorption cross-section at 980 nm, leading to efficient absorption of infrared (IR) or near-infrared (NIR) pump photons and subsequently transfer their harvest energy to neighboring activator ions.…”
Section: 2mentioning
confidence: 99%